Osteosarcoma with cytokeratin expression: a clinicopathological study of six cases with an emphasis on differential diagnosis from metastatic cancer. Issue 10 (26th September 2003) - Okada, K; Hasegawa, T; Yokoyama, R; Beppu, Y; Itoi, E
Abstract : Aims: To clarify the clinicopathological profile of osteosarcomas showing an intensely positive immunoreaction for cytokeratin. Methods: Clinicopathological and immunohistochemical features were analysed in 131 patients with non-metastatic, conventional osteosarcoma, treated in Akita University and National Cancer Centre in Tokyo between 1972 and 1999. Results: Six patients (4.5%; mean age, 32 years; four men, two women) had osteosarcomas showing intense cytokeratin expression. Tumours were located on the long bones of the extremities in five patients and the ilium in one. Osteoid formations were found in biopsied specimens in all cases. Three tumours were classified as osteoblastic osteosarcoma, two as fibroblastic, and one as chondroblastic. In three tumours classified as the osteoblastic subtype, epithelioid features were prominent, and four tumours showed pronounced cellular pleomorphism. In contrast to the expression of cytokeratin, epithelial membrane antigen was negative in all cases. Surgery with a wide excisional margin was performed in six patients. Preoperative and postoperative chemotherapy was given to five of the six patients, but the effects of these agents were negligible. Three of the six patients developed lung metastases, whereas the other three patients have remained well with no evidence of local recurrence or distant metastasis. Conclusions: Osteosarcoma with intense immunoreaction for cytokeratin was rare. The clinicopathological features were similar to those of patients with conventional osteosarcoma, except for a higher age, chemotherapy resistance, histological epithelioid features, and pleomorphism. This study indicates that osteoid formation and negative expression of epithelial membrane antigen are key features in the differentiation from metastatic carcinoma.